2020
DOI: 10.3390/jcm9020380
|View full text |Cite
|
Sign up to set email alerts
|

Ensemble Learning to Improve the Prediction of Fetal Macrosomia and Large-for-Gestational Age

Abstract: Background: The objective of this study was to investigate the use of ensemble methods to improve the prediction of fetal macrosomia and large for gestational age from prenatal ultrasound imaging measurements. Methods: We evaluated and compared the prediction accuracies of nonlinear and quadratic mixed-effects models coupled with 26 different empirical formulas for estimating fetal weights in predicting large fetuses at birth. The data for the investigation were taken from the Successive Small-for-Gestational-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 33 publications
(38 reference statements)
0
11
0
Order By: Relevance
“…Prenatal ultrasound imaging was another subject of research. Ye et al aimed to investigate whether using ensemble methods on ultrasound measurements could improve the prediction of fetal macrosomia [ 17 ]. They concluded that ensemble learning, especially voting and stacking, can improve the prediction of fetal macrosomia and, as such, has the potential to assist obstetricians in making clinical decisions [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Prenatal ultrasound imaging was another subject of research. Ye et al aimed to investigate whether using ensemble methods on ultrasound measurements could improve the prediction of fetal macrosomia [ 17 ]. They concluded that ensemble learning, especially voting and stacking, can improve the prediction of fetal macrosomia and, as such, has the potential to assist obstetricians in making clinical decisions [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…The most objective method currently employed to estimate fetal body weight is ultrasonographic (US) measurement, which encompasses over 30 different formulas for the US estimates to predict newborn birth weight [16][17][18], with the most widely used being the Hadlock formula [19]. To generate sonographic fetal weight estimations with a lower error margin, many formulas have reflected disparate parameters of the fetus (fetal abdominal fat layer [20], shoulder soft-tissue thickness [21], biacromial diameter [22]), and some have even entailed 3D sonographic measurements [23].…”
Section: Discussionmentioning
confidence: 99%
“…Shigemi et al created a scoring system based upon the significant predictors of macrosomia without sonographic information [4], and their system exhibited a high negative predictive value of 0.996-1.000, while the positive predictive value for screening macrosomia was extremely low (0.003). Zou et al [27] and Kang et al [28] published models that could only be applied to women with GDM rather than to all pregnant women, and Ye et al used ensemble methods (one comprising a machinelearning algorithm) to improve the prediction of fetal macrosomia [18]. Unfortunately, ensemble methods are cumbersome and limited in their practicability.…”
Section: Discussionmentioning
confidence: 99%
“…This study explored the key variables of depressive disorders in female older adults living alone using the stacking ensemble technique. A number of studies (14,15,22) have reported that the stacking ensemble model shows excellent accuracy because it compensates for the overfitting possibility, a disadvantage of a single predictive model. In other words, the goal of the stacking ensemble is to improve generalization capacity, and it has been widely used for classifying and developing predictive models using machine learning.…”
Section: Exploring the Best Predictive Factors For Depressive Disorders Using Stacking Ensemble: Base Modelmentioning
confidence: 99%